SIFAT FISIK DAN SIFAT KIMIA TANAH ASOSIASI HAPLUDANDS-EUTRUDEPTS PADA LAHAN BERBATU APUNG DI KECAMATAN MONTONG GADING LOMBOK TIMUR - Selviya Rosita; Baharuddin Abu Bakar; Mahrup (Department of Soil Science, Faculty of Agriculture, University of Mataram, 2023)
This study aims to determine the value of the physical and chemical properties of the soil association hapludands-eutrudepts on ex-mined pumice land and non-mined land. This research was conducted in the District of Montong Gading and the Physics Laboratory and Soil Chemistry Laboratory, Faculty of Agriculture, University of Mataram in July 2022. The method used in this study was a descriptive method with survey techniques in the field accompanied by soil sampling supported by soil analysis in the laboratory and data collection. secondary data are land use maps and administrative maps. Parameters of soil physical observation are soil texture and porosity. Parameters observed in soil chemistry were pH (Electrometric Method), total-N (Kjedahl Method), available-P (Bray II Method) and K-exchanged (pH 7 Extractor). The results showed that the soil at the study site had a sandy loam and loamy sand texture and had relatively the same porosity level. The research soil has a slightly acidic pH except for the non-mined service which has a neutral pH, nitrogen content of the research soil had low nitrogen content on non-mined land and very low on ex-mined land, phosphor content The research soil has a very high phosphor content except for ex-mining plantations which have high phosphor and potassium content of Pelitian soil has moderate potassium content except for ex-mining settlements which have high potassium.